Effects of The Black cumin seeds (Niqella sativa Linn.) on Endometrial Mucins of Mature Rats; Histochemical Study - Hassan, Ahmed J.; Al-Baffar, Raith A.B.; Al-Baghdadi, Haythem A.; Al-Azawi, Hani T. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: Nitre I la sativa Linn is a well known herb that is used by different societies, as food additive and as a medicinal herb: it used as a galactagouge for lactating women, and has long been described as an abortifacient-emmenagouge. Aim of the work: is to investigate the effect of crude black seeds on the endometrium and the pattern of it’s mucins, during the different phases of the Estrus cycle, making use of some special stains for the histochemical demonstration of mucins. Materials <6 Methods.’Crude Nieella sativa Linn, seeds were administrated for ten days, by an orogastric tube, on single regular daily dosage to properly selected mature Norway albino female rats. Animats were subdivided into subgroups, according to phases of the estrus cycle. Utera of these animals were routinely processed for carbohydrate histochemical (d-PAS, d AB2.5-PAS & A li 1.0) studies using carnoy’s fixative, paraffin embedded sections. Experimental specimens were compared with that of control subgroups. Results: Results showed marked production of diastase fast-PAS reactive non-alcianophilic neutral mucins, with inhibited production of sulphated highly acidic mucins among the surface lining and the glandular epithelial cells, at Estrus. Effects of such changes in the pattern of endometrial mucins on the state of fertility, was discussed.